THE IMPACT OF THE 2018 UK CORPORATE GOVERNANCE CODE ON THE FINANCIAL PERFORMANCE OF LISTED FIRMS IN THE UNITED KINGDOM - Grant, Cephas Paa-Kwesi (2022)
The Financial Reporting Council (FRC) recently introduced a new UK Corporate Governance Code in 2018 to replace the 2016 code. The code has been designed to set higher corporate governance standards in the UK to help attract long-term investments as well as boost business integrity and openness which will benefit the economy. This study aims at ascertaining how the revised corporate governance regulations have impacted the financial performance of UK listed firms after the 2018 Code was introduced by comparing the pre and post periods of the code. The FTSE 100 firms were used as the sample and secondary data were obtained from their annual reports, FAME UK and BoardEx. Firm selection was determined by the availability of data for the pre-and post-code periods including those who complied. The data was analyzed using the Stata statistical software. The study investigates the relationship between the board’s characteristics (gender diversity, age diversity, chair tenure, and remuneration) and the financial performance (measured by ROA and ROE). Based on a total sample of 116 observations in both periods, Ordinary Least Squares (OLS) regression was used to test the hypotheses established for the FTSE 100 firms. The findings show that age diversity, chair tenure and remuneration have an insignificant relationship with financial performance while only gender diversity shows a significant positive relationship with performance before the amendments of the 2018 code. Meanwhile, age diversity, gender diversity and chair tenure have an insignificant relationship with performance, but remuneration shows a significant positive relationship with financial performance after the amendments of the 2018 code. The study concludes that just one corporate governance mechanism enhanced financial performance after the reforms, and this justifies that the impact of the code has not been substantial. Additionally, it should be noted that the findings determined in this study are likely to be of use to academics, regulators, practitioners, and policymakers. By my reckoning, this study is the first to examine the impact of the 2018 code on the financial performance of listed UK firms after its introduction.